Divorce and Its Impact on Custody of Minors Using Islamic Law Perspectives - Nurjanah, Siti (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study aims to examine the factors that cause divorce in an Islamic country and how that affects the custody minors shares between parents from an Islamic perspective. This study focus on three main causes, adultery, economy, and the occupance gap. Furthermore, this research used interviews of 718 married couples 140 pairs are divorced in Kota Metro, a high rate of divorce region with a Muslim majority in an Islamic country (Indonesia). The results of this study show that Couples sometimes have to face problems in their domestic life, the emergence of problems in the household can be caused by many things including economic factors, and no sense of responsibility, differences in life outlook that can lead to household crises. The woman who will become a widow does not think about other people's views of her because she thinks this is her life and she is the one who goes through it all, it's just that there is guilt in her child when she has to divorce.Â  He thinks about the impact of divorce that will arise on the psychological development of his child, he tries so that his child does not lose the love of a father.